Correlation between Happy Planet Index with Education on the Example of Russia and Austria; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Kats V. M. Vadim Markovich (2016, 2016)
Title screen